The transrepressive activity of peroxisome proliferator‐activated receptor alpha is necessary and sufficient to prevent liver fibrosis in mice. Issue 5 (1st October 2014) - Pawlak, Michal; Baugé, Eric; Bourguet, William; De Bosscher, Karolien; Lalloyer, Fanny; Tailleux, Anne; Lebherz, Corinna; Lefebvre, Philippe; Staels, Bart
<x xml:space="preserve">Abstract</x> Nonalcoholic fatty liver disease (NAFLD) is increasingly prevalent and strongly associated with central obesity, dyslipidemia, and insulin resistance. According to the multiple‐hit model of NAFLD pathogenesis, lipid accumulation drives nonalcoholic steatohepatitis (NASH) initiation by triggering oxidative stress, lipotoxicity, and subsequent activation of hepatic inflammatory responses that may progress, in predisposed individuals, to fibrosis and cirrhosis. While there is an unmet therapeutical need for NASH and fibrosis, recent preclinical studies showed that peroxisome proliferator‐activated receptor (PPAR)‐α agonism can efficiently oppose these symptoms. To dissect the relative contribution of antisteatotic versus anti‐inflammatory PPAR‐α activities in counteracting dietary‐induced liver fibrosis, we used a PPAR‐α mutant lacking its DNA‐binding‐dependent activity on fatty acid metabolism. Liver‐specific expression of wild‐type or a DNA‐binding‐deficient PPAR‐α in acute and chronic models of inflammation were used to study PPAR‐α's anti‐inflammatory versus metabolic activities in NASH and fibrosis. Pharmacologically activated PPAR‐α inhibited hepatic inflammatory responses and the transition from steatosis toward NASH and fibrosis through a direct, anti‐inflammatory mechanism independent of its lipid handling properties. Conclusion: The transrepression activity of PPAR‐α on chronic liver inflammation is sufficient to prevent progression of NASH to liver fibrosis. Dissociated PPAR‐α agonists, selectively modulating PPAR‐α transrepression activity, could thus be an option to prevent NASH and fibrosis progression. (Hepatology 2014;60:1593–1606)